White-tailed deer (Odocoileus virginianus) carcass survey following an aerial 1080 operation, Otago, New Zealand. Issue 2 (3rd April 2021) - Pinney, Kaylyn A.; Ross, James G.; Paterson, Adrian M.
ABSTRACT: Intensive ground-based searches for white-tailed deer carcasses were conducted in the Dart Valley/Routeburn catchments following the aerial application of 1080 (sodium fluoroacetate) cereal pellets as part of the 'Battle for the Birds'/ Tiakina Ngā Manu predator control program in August 2014. Four 100 ha areas were searched over four days. The detection rate of simulated carcasses allowed an estimation of the success rate for finding deer carcasses. All white-tailed deer carcasses located were confirmed to have muscle tissue containing traces of 1080 (range: 0.41–1.06 mg/kg). The detection rate of simulated carcasses was 78% (312/400). The adjusted number of dead white-tailed deer was 3.85 ± 0.85 (95% CI) over the 400 ha (0.96 deer/km 2 ) suggesting a potential mortality of 146 ± 32 (95% CI) white-tailed deer in the predator control area of 15, 215 ha. These results suggest that recurrent predator control operations may have implications for sustainable hunting of white-tailed deer.